Panzerina lanata accelerates methicillin-resistant Staphylococcus aureus eradication by promoting migration and activation of neutrophils - Dong, Shuai; Bai, Xingyuan; Chen, Bin; Fan, Minzhe; Liu, Qi; Zhao, Yubo; Li, Linsen; Zhu, Dan (Frontiers in Pharmacology, 2025)
BackgroundPanzerina lanata (Lanata) is generally used to treat pustule infection in Inner Mongolia folk medicine and is called “the holy medicine for pustule.” However, the pharmacological mechanism of Lanata in treating pustule infection is still unclear.AimsThis study aimed to investigate the therapeutic effects of Lanata on skin infection and explore the underlying mechanisms.MethodsA skin wound methicillin-resistant Staphylococcus aureus (MRSA) infection mouse model was established to evaluate the healing effect of Lanata on infected wounds. In vitro assays were also conducted to determine the antibacterial activity of Lanata. Flow cytometry and immunohistochemistry were used to dynamically detect the number of neutrophils in the bone marrow, peripheral blood, and MRSA-infected wound. Protein expression in the infected wound skin was detected by a protein chip. Using an air pouch MRSA infection mouse model, the number of neutrophils, reactive oxygen species (ROS) level in neutrophils, and neutrophil extracellular trap (NET) formation were dynamically detected by flow cytometry and immunofluorescence. RNA-seq, RT-qPCR, flow cytometry, ELISA, and CXC chemokine receptor 2 (CXCR2) and P-selectin glycoprotein ligand-1 (PSGL-1) inhibitors were used to explore the mechanism of Lanata in regulating neutrophils.ResultsIn vitro assays showed that Lanata had no direct antibacterial activity. In skin wound MRSA-infected mouse, Lanata promoted the rapid migration of neutrophils from the bone marrow via peripheral blood to the wound site to eradicate MRSA in the acute stage of infection and accelerate wound healing. Skin protein chip analysis showed that Lanata upregulated CXCR2 and PSGL-1 protein levels in skin wounds. Furthermore, analysis using the air pouch MRSA infection mouse model found that Lanata not only promoted the rapid migration of neutrophils from peripheral blood to the air pouch but also enhanced the activation of neutrophils, including the increase of ROS and the release of NETs, and upregulated the expression of CXCR2, PSGL-1, and myeloperoxidase (MPO) in neutrophils. Inhibition of CXCR2 and MPO significantly attenuated the effect of Lanata on promoting migration and activation of neutrophils.ConclusionPanzerina lanata resists MRSA infection by promoting migration and activation of neutrophils to rapidly eradicate MRSA.